Analisis kemampuan berpikir kreatif matematis pada siswa kelas VII SMPN 1 parongpong dalam menyelesaikan soal bangun datar - Syahpitri, Dita; Chotimah, Siti (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
Thinking Mathematical creativity is a thinking skill whose goal is to solve a problem with several ideas, generate various ideas, be able to create new habits and have nothing in common with others and be able to develop ideas. Indicators of students' mathematical creative thinking abilities include 4 aspects, namely fluency, flexibility, originality and elaboration. The purpose of this study was to determine the ability to think creatively in class VII junior high school students in solving flat shape problems. This research is a descriptive qualitative research. The test used in this test is a creative thinking test which presents questions to students in class in the form of a written test in grade VIII of a SMPN 1 Parongpong school. The results of the research show that the students' creative reasoning in a system of linear equations is still weak, because the students' answers are correct. gets the maximum score, fluency index is 45%, flexibility is 45%, originality is 29%, and the lowest percentage is elaboration which is 3%. This is an indicator of unfulfilled student progress.